Litterature for children and young readers on the internet: from Cervantes Virtual - Rovira Collado, J. (Ocnos, 2011)
Faced with the constant innovations that internet offers us and the transformations that they pressumed in the reading process, the following study describes the current status of Children and Youth Literature (LIJ) in Spanish on the web through two models, not opposite but complementary. First, the big portals and institutional projects, such as the LIJ section of the Virtual Library Miguel de Cervantes, which offers classical texts, author libraries and an important theoretical apparatus. Secondly, under the definition of LIJ 2.0, all the displays of the LIJ that we can find through the various options offered by the Social Web, better known as Web 2.0, where the participation of individual users and the interaction among them are the fundamental characteristics. Blogs, Wikis or Social Networks are the axes of our study to know the presence of the LIJ and the possible applications that they offer. Our approach, from the teaching of language and literature, seeks to describe both realities and the specific possibilities of each tool to integrate the use of the internet with the dissemination and the study of the LIJ.